Meningococcal Urethritis: an additional Source of Meningococcal Disease? - N. N. Kostyukova; V. A. Behalo (Эпидемиология и вакцинопрофилактика)
Background. Beginning with the middle of the XX century some observations about cases of meningococcal urethritis have appeared. The number of articles for such subjects has promptly increased in the last decade of XXI. The epidemiological features of meningococcal urethritis are slightly understood. Aims. A review of the latest publications on meningococcal urethritis is presented. Particular attention is given to outbreaks of meningococcal urethritis caused by the new genetic clade USNmCU of N.meningitidis, which occurred in several US states in 2013-2016. Conclusions. The isolates from patients were non-capsulated and belonged to the CC-11 clonal complex, the most virulent among N.meningitidis strains of serogroups B, C, Y, W. The orogenital transmission of clade strains has been proven. It is assumed that N.meningitidis acquired genes for anaerobic growth as a result of genetic recombination during co-presence with N. gonorrhea on the mucous membranes and became to be able to colonize the urogenital tract. The urethritogenic meningococcal clade is the result of the adaptation of the capsular strain of meningococcus serogroup C of the clonal complex CC-11, which is responsible for outbreaks of generalized meningococcal infection in MSM communities. The urethritogenic strains are considered as representatives of the emergent clade of N. gonorhoeae. Their ability to be transmitted through direct sexual contact is unknown. The epidemiological role of the clade in the spread of meningococcal infection is discussed. It is necessary to develop the researches concerning the epidemiological features of meningococcal urethritis and its additional role as the source of meningococcal disease.